Development and Automation of a Photovoltaic-Powered Soil Moisture Sensor for Water Management - de Melo, Denilson Alves; Silva, Patrícia Costa; da Costa, Adriana Rodolfo; Delmond, Josué Gomes; Ferreira, Ana Flávia Alves; de Souza, Johnny Alves; de Oliveira-Júnior, José Francisco; da Silva, Jhon Lennon Bezerra; da Rosa Ferraz Jardim, Alexandre Maniçoba [UNESP]; Giongo, Pedro Rogerio; Ferreira, Maria Beatriz; de Assunção Montenegro, Abelardo Antônio; et al. (MDPI, 2023)
The objective of this study was to develop and calibrate a photovoltaic-powered soil moisture sensor (SMS) for irrigation management. Soil moisture readings obtained from the sensor were compared with gravimetric measurements. An automated SMS was used in two trials: (i) okra crop (Abelmoschus esculentus) and (ii) chili pepper (Capsicum frutescens). All sensors were calibrated and automated using an Arduino Mega board with C++. The soil moisture data were subjected to descriptive statistical analysis. The data recorded by the equipment was correlated with the gravimetric method. The determination coefficient (R2), Pearson correlation (r), and root mean square error (RMSE) were adopted as criteria for equipment validation. The results show that our SMS achieved an R2 value of 0.70 and an r value of 0.84. Notably, there was a striking similarity observed between SMS and gravimetric data, with RMSE values of 3.95 and 4.01, respectively. The global model developed exhibited highly efficient outcomes with R2 (0.98) and r (0.99) values. The applicability of the developed SMS facilitates irrigation management with accuracy and real-time monitoring using digital data. The automation of the SMS emerges as a real-time and precise alternative for performing irrigation at the right moment and in the correct amount, thus avoiding water losses.
Keywords: automation; soil moisture; solar energy; tensiometer